Clinical association between the metabolite of healthy gut microbiota, 3-indolepropionic acid and chronic kidney disease. Issue 6 (December 2019) - Sun, Chiao-Yin; Lin, Cheng-Jui; Pan, Heng-Chih; Lee, Chin-Chan; Lu, Shang-Chieh; Hsieh, Yu-Ting; Huang, Shih-Yi; Huang, Hui-Yu
Summary: Background & aims: Emerging evidence indicates that gut microbiota serves an important role in the development and progression of chronic kidney disease (CKD). Changes to the gut microbial flora can cause the generation of uremic toxins, which contribute to chronic kidney injury. The aim of the current study was to explore the clinical association between metabolites and CKD. Methods: Between August 2013 and January 2015, a two-phase case–control study was conducted to analyze the clinical association between metabolites and CKD in a community health program. The first phase of the study was a prospective case–control survey designed for comparing the differences in the metabolome profile of patients with (n = 10) and without (n = 10) estimated glomerular filtration rate (eGFR) rapid decline (a yearly decline >20%). The second phase of the study was a cross-sectional case–control study, which checked and compared the metabolites, indoxyl sulfate and p-cresol sulfate levels between healthy subjects (n = 144) and CKD patients (n = 140). Results: In the first phase of the study, it was revealed that IPA levels of patients with rapid renal function decline were significantly reduced compared with the control patients (n = 10 for each group). The second phase furthered checked and compared the IPA, indoxyl sulfate and p-cresol sulfate levels between healthy subjects (n = 144) and CKD patients (n = 140). The results showed that the average level of indoxyl sulfate (2738.2 vs . 541.0 ng/ml, P  < 0.01) and p-cresol sulfate (1442.8 vs . 1394.6 ng/ml, P  < 0.01) were significantly higher in the CKD patients, while the average level of IPA was significantly higher (49.8 vs . 34.7 ng/ml, P  < 0.01) in the control patients. Conclusions: Our results suggest that IPA might be an important biomarker and renal protector against the development of CKD. Highlights: The study suggests the impact of serum IPA on renal function decline rate. Significant clinical correlation between IPA and the chronic kidney disease. Circulating IPA level is a predictor for development of chronic kidney disease.